A Strategy to Provide a Present and Future Scenario of Mexican Biodiversity of Tardigrada - Jazmín García-Román; Alba Dueñas-Cedillo; Montserrat Cervantes-Espinoza; José Juan Flores-Martínez; Carlos Fabián Vargas-Mendoza; Enrico Alejandro Ruiz; Francisco Armendáriz-Toledano (Diversity, 2022)
Although the number of known tardigrade taxa in Mexico has increased significantly in the last ten years, the knowledge of their diversity faces challenges, as more than half of the Mexican territory has no records of this phylum. Thus, we developed a strategy to provide a present and future scenario for understanding the Mexican biodiversity of Tardigrada, described the distribution patterns of the current recorded species, calculated the estimated richness, and the estimated taxonomic effort needed to complete the national inventory. We obtained 474 records of 105 taxa, belonging to 42 genera and 75 species, distributed in 12 of the 14 biogeographical provinces of Mexico. We found that 54.72% of the species are present in more than three world regions and 3.79% of species that have been recorded only in Mexican provinces. Distribution patterns could be recognized for 11 species, two of which have a Nearctic distribution, seven are Neotropical and two are distributed in both regions. The Mexican biogeographical provinces with the greatest diversity of tardigrades, both at specific and generic level, were the Transmexican Volcanic Belt (TVBP) and the Sierras Madre Oriental (SMOrP) and Sierra Madre Occidental (SMOcP), which have been previously identified as particularly species-rich regions. Diversity estimation methods predict that more than 290 species of tardigrades could be found in Mexico.